2002
DOI: 10.1089/107555302317371424
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Pharmacokinetics of an Extract of Isoflavones from Red Clover (Trifolium pratense)

Abstract: Isoflavones have pharmacokinetic characteristics that suggest that once-daily administration is adequate when they are administered long-term as dietary supplements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
32
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 15 publications
2
32
0
1
Order By: Relevance
“…In a study reported by Setchell et al, (2003), higher doses of isoflavones did not produce linear pharmacokinetic parameters, suggesting that uptake was rate -limiting and saturable. Administration of approximately 80mg isoflavones a day is thought to give concentrations of genistein and daidzein consistent with that found in patients on a high isoflavone diet (Howes et al, 2002).…”
Section: Pharmacologysupporting
confidence: 65%
“…In a study reported by Setchell et al, (2003), higher doses of isoflavones did not produce linear pharmacokinetic parameters, suggesting that uptake was rate -limiting and saturable. Administration of approximately 80mg isoflavones a day is thought to give concentrations of genistein and daidzein consistent with that found in patients on a high isoflavone diet (Howes et al, 2002).…”
Section: Pharmacologysupporting
confidence: 65%
“…Although serum genistein concentrations were not measured in the current trial, a strong increase in serum genistein concentrations was observed in the majority of men in the male counterpart of this trial after similar isoflavone intervention with comparable compliance (20). In that trial, serum genistein concentrations were within the range of those of subjects traditionally consuming a high-isoflavone soybased diet (24). Furthermore, we assessed factors which are thought to potentially influence circulating concentrations of IGFs and IGFBPs (e.g., total energy and protein intake, consumption of products rich in isoflavones and lycopene, body weight, and physical activity).…”
Section: Discussionmentioning
confidence: 51%
“…In humans, BCA has poor bioavailability mainly due to extensive first-pass metabolism and biliary elimination, although the absorption of BCA is rapid because of its high permeability (32). The concentrations of BCA achieved in human plasma following dietary administration tend to be in the low nM range (10-20 nM; 33,34), whereas the concentrations following the oral ingestion of dietary supplements (herbal preparations) are above 100 nM (35). These concentrations in human plasma obtained after dietary supplement ingestion, based on our study findings, may be high enough to observe the chemopreventive effects of BCA.…”
Section: Discussionmentioning
confidence: 99%